OPTIMIZATION OF KOARMADA I OPERATION PATTERN IN FACING THREAT OF TERRITORIAL VIOLATION IN NATUNA SEA WATERS - Yoyok Eko Hadi Wijaya; Avando Bastari; Abdul Rachman (Indonesian Naval Technology College STTAL, 2020)
ABSTRACT Operation to secure border areas is an effort and activity to ensure the upholding of state sovereignty at land, sea and air borders with other countries, from all forms of threats and violations including survey and mapping activities. The limited ability of the KRI and the budget provided by the state as well as the need for security of Indonesia's maritime border areas, resulted in the need for a demand for thoughts on optimizing the deployment of KRI at the Aju bases and the operations sector in Natuna Sea waters, by taking into account the type of KRI, speed, endurance, radar coverage and costs. operation. So that the resulting composition of the KRI deployment at the initial base and the border area security operations sector in the waters of the Natuna Sea. This research discusses the optimization of the deployment of KRI at the initial base and in the operational sector in border area security operations in the Natuna Sea waters, to provide an optimal compromise solution between two different objective functions, namely coverage area and operating costs. This problem solving uses the Competitive Profile Matrix approach with the help of superdecision software for weighting the objective function. While the optimization of the KRI power distribution uses the transshipment model method, Goal Programming and Weighted Goal Programming, where all algorithms of the approach are resolved silmutaneously in a syntax using Lingo 11 optimization software.The result of this optimization is that the average coverage area effectiveness is achieved. 450,913 mil2 and the average operating cost efficiency is 40% of the stipulated budget. Keywords : Border Area Security Operations, CPM, Optimization Model, Transshipment, Goal Programming, Weighted Goal Programming, Coverage Area, Operating Costs.